Monitoring Cultural Heritage Sites Affected by Geohazards in Cyprus Using Earth Observation - Themistocleous, Kyriacos (My University, 2023)
Monitoring geo‐hazards of cultural heritage sites and structures as well as the surrounding archeo‐ landscapes facilitates the early recognition of potential risks and enables effective conservation, monitoring and planning. Landslides, earthquakes and erosion are the predominant geo‐hazards in Cyprus. In order to identify and monitor geohazards and environmental displacements, Earth Observation techniques can be used in combination with long‐term low‐impact monitoring systems, such as UAVs and geodetic techniques to monitor and assess the risk from geohazards on cultural heritage sites and structures to evaluate potential changes and risks.
Keywords: Cultural Heritage; Geo-hazards; Earth observation monitoring